Peces ligados a Thalassia testudinum en el arrecife Lobos, Veracruz, México: diversidad y abundancia - González, Carlos (2006)
The diversity and abundance of ichthyofauna associated with Thalassia testudinum in the Lobos coral reef, Veracruz, Mexico, were studied in September and October 2002. Thirty six visual censuses in four sample sites were made using a 50 x 2 m transect belt. On each census, fish species, abundance and size were recorded. Leaf size and cover of T. testudinum were estimated. The similarity of fish groups was calculated with the Gower coefficient. The most abundant coral reef fishes were: Scarus iseri, Halichoeres bivittatus, Sparisoma radians, Stegastes adustus and Stegastes leucostictus. The highest density (0.04078 ind/m2) and biomass (0.72408 g/m2) of fish species were recorded in site II, where leaf size was greater (30.8 cm). The analy-sis of variance showed significant differences between sites in leaf size (F=18.30856; p=0.00001) and cover (H=33.8119; p=0.00001). These differences suggest a relationship between fish diversity and abundance, and T. testudinum leaf size and cover. The Gower similarity index produced two groups of fishes; one of them (site II) showed the highest abundance. In this reef, the fishes associated to sea grasses seem to reflect the characteristics of T. testudinum.